Population management, RH law, and inclusivity - Ernesto M. Pernia (University of the Philippines, School of Economics (UPSE), 2014)
Taking off from the self-evident fact that the population variable centrally figures in both labor and product markets, this paper argues that the growth rate of population, its age structure and spatial distribution should be key considerations in a country's development strategy to promote rapid and sustained economic growth, full employment, poverty reduction, and social inclusion. This represents a shift from the inordinate emphasis on the demand for labor, i.e., job creation. Significantly reducing unemployment and poverty can be achieved not solely through job generation but also by managing the quantity and quality of the work force, which is determined, with a lag, by the growth rate and structure of the population. The paper provides a perspective on population as it impacts the labor market and poverty. It then discusses issues of fertility and unmet needs for family planning and reproductive health services in relation to poverty. A sidelight on pressing concerns (gender-based violence and lack of RH services) brought about by Super-typhoon Yolanda is presented. This is followed by a glimpse into regional experience in population policy, family planning and poverty as exemplified by Thailand and Bangladesh. The penultimate section provides simulations and projections using different assumptions of contraceptive prevalence rates that result in various scenarios of fertility and population growth.
Keywords: J1; J2; J6; O1; O2; 330; Demographic economics; Demand and supply of labor; Unemployment and mobility; Economic development; Development planning and policy; Poverty and inclusive growth; Philippines; Asia